Reaksi Isomerisasi Î±-Pinena Minyak Terpentin dengan Katalis Zr-Zeolit Alam menggunakan Microwave - Hutasoit, Parpulungan; Wijayati, Nanik; Mahatmanti, F. Widhi (Indonesian Journal of Chemical Science, 2018)
In efforts to increase economic value of turpentine oil is perform transformation of Î±-pinena into derivation through isomerization reaction. Catalytic isomerization reaction use catalysts Zr-Natural zeolite and characterization the catalyst include analysis of crystallinity by X-Ray Diffraction (XRD) and Surface Area Analyzer (SAA). Isomerization reaction in the microwave with 10 mL turpentine oil reacted and 0.5 g catalysts. The reaction conduct by the variation of the microwave power 320, 480, and 640 watts and variation of reaction time of 5, 10, 15, 20, and 25 minutes. The reaction products of the compounds tested using IR, GC, and GC-MS. The result research gain isomers such as camphene, 3-carene, Î±-terpinene, limonene, p-cymene, Î²-pinene, and terpinolene. Increase power the microwave yields increase the concentration of the compound isomers product, whereas the reaction time to increase conversion Î±-pinena into isomer compound. The ideal condition in study, found to be microwave power of 640 watts and 15 minutes, yield conversion of Î±-pinene 29.907 %.